Sustainable Future Energy Technology and Supply Chains A Multi-perspective Analysis - Cucchiella, Federica; Koh, Lenny (Green Energy and Technology, 2015)
This book provides a valuable resource for anyone who wishes to understand how sustainable use of energy can lead to increased efficiency of industrial supply chains and improved financial profitability. The book is organized around real examples and case studies that can be applied to real-world problems. Furthermore, insight is provided by an international panel of contributors, and the book provides comprehensive coverage of current practice and future developments in the evolution of sustainable supply chains and energy consumption. The text underlines how organizations are now looking seriously at supply chain assets in order to help their suppliers retool and focus on renewable energy. Renewable energy technology is a fast growing market with promising financial returns and substantial environmental gains; this book shows how the right management of renewable investments can have significant advantages by: • providing critical opportunities in driving costs down and making renewable energy sources more competitive with conventional energy; • making infrastructure expansion easier; • increasing employment in manufacturing and services supply chains in order to support renewable energy generation; and • mitigating the impacts of climate change. This book is intended for business professionals, researchers and students working in supply chain management or energy management.